Safe handling of gases - Safetycare Australia Pty. Ltd. ([S.l.] : Safetycare Australia, 1992)
Described gas cylinders supply a wide variety of gases for a multitude of different industrial, medical and domestic purpose
Accompanied by 1 trainer's manual
Keywords: Gases -- Safety measures